Metallo-polyelectrolytes as a class of ionic macromolecules for functional materials. Issue 1 (December 2018) - Zhu, Tianyu; Sha, Ye; Yan, Jing; Pageni, Parasmani; Rahman, Md; Yan, Yi; Tang, Chuanbing
Abstract The fields of soft polymers and macromolecular sciences have enjoyed a unique combination of metals and organic frameworks in the name of metallopolymers or organometallic polymers. When metallopolymers carry charged groups, they form a class of metal-containing polyelectrolytes or metallo-polyelectrolytes. This review identifies the unique properties and functions of metallo-polyelectrolytes compared with conventional organo-polyelectrolytes, in the hope of shedding light on the formation of functional materials with intriguing applications and potential benefits. It concludes with a critical perspective on the challenges and hurdles for metallo-polyelectrolytes, especially experimental quantitative analysis and theoretical modeling of ionic binding. Polyelectrolytes are a class of macromolecules containing charged groups. Here the authors review properties and functions of metallo-polyelectrolytes to shed light on how to harness fundamental physiochemical properties for applications in biomedical sciences and advanced materials.